The Role of Servant Leadership on Employee Performance Mediated by Work Motivation Within Millennials - Adrial, Fikry; Rafli, Muhammad; Maharani, Anita (Husnayain Business Review, 2025)
Purpose - The purpose of this study is to examine the role of servant leadership in employee performance within millennials, both directly and mediated by work motivation. This study refers to several studies on servant leadership, employee performance, and work motivation. Methodology- This study uses a quantitative research approach, with data collection techniques by distributing surveys to employees working in a public organization in the Sumatra area, Indonesia, as the phenomena was found in this area. Samples received after several weeks of distributing questionnaire was 83. The technique of analysis of this research adopting partial least square structural equation modelling. Finding - The results of this study indicate that employee performance is influenced by servant leadership, both directly and mediated by work motivation; in other words, employees will perform well if driven by the external and internal roles of the individual. Originality - This study offers originality by examining the direct and mediated effects of servant leadership on employee performance specifically within the context of millennials working in a public organization in the Sumatera area. While previous research may have explored these relationships in other contexts, this study's focus on a specific generation and geographical location in Indonesia provides a unique contribution to the literature. Furthermore, the study highlights the interplay between external (servant leadership) and internal (work motivation) drivers of employee performance, offering practical implications for organizations seeking to enhance employee effectiveness. Practical implications - The implication of this study is that organizations can provide stimuli in the form of encouragement for individuals to realize the importance of self-motivation if it is obtained from their superiors.